New integrated care models in England associated with small reduction in hospital admissions in longer-term: A difference-in-differences analysis. Issue 8 (August 2020) - Morciano, Marcello; Checkland, Katherine; Billings, Jenny; Coleman, Anna; Stokes, Jonathan; Tallack, Charles; Sutton, Matt
Highlights: Integration policies are often seen as strategies to reduce avoidable hospital activity. "New care models" were piloted in England under the "Vanguard" initiative. We evaluate the efficacy of the Vanguard programme in reducing hospital utilisation. The Vanguard initiative slowed the rise in emergency admissions observed in England. The reduction occurred mainly in care home sites, at the programme's end. Abstract: Closer integration of health and social care services has become a cornerstone policy in many developed countries, but there is still debate over what population and service level is best to target. In England, the 2019 Long Term Plan for the National Health Service included a commitment to spread the integration prototypes piloted under the Vanguard `New Care Models' programme. The programme, running from 2015 to 2018, was one of the largest pilots in English history, covering around 9 % of the population. It was largely intended to design prototypes aimed at reducing hospital utilisation by moving specialist care out of hospital into the community and by fostering coordination of health, care and rehabilitation services for (i) the whole population ('population-based sites'), or (ii) care home residents ('care home sites'). We evaluate and compare the efficacy of the population-based and care home site integrated care models in reducing hospital utilisation. We use area-level monthly counts of emergency admissions and bed-days obtained from administrative data using a quasi-experimental difference-in-differences design. We found that Vanguard sites had higher hospital utilisation than non-participants in the pre-intervention period. In the post-intervention period, there is clear evidence of a substantial increase in emergency admissions among non-Vanguard sites. The Vanguard integrated care programme slowed the rise in emergency admissions, especially in care home sites and in the third and final year. There was no significant reduction in bed-days. In conclusion, integrated care policies should not be relied upon to make large reductions in hospital activity in the short-run, especially for population-based models.